Digitisation, Lossy Compression And Visualisation In Cost-Effective Telehealth Environment - Choong , Miew Keen (2004)
Digital technology in medical imaging has become increasingly important. In recent years, more and more investment have been made in this field. With the emergence of paperless hospitals and the advent of telehealth and telemedicine applications, the importance of digital manipulations has become even greater. Undoubtedly, digital technology greatly benefits the radiology department. However, these benefits come at a price. The cost of the equipment remains an expensive proposition for now. Thus, action must be taken to lower the financial burden, especially to clinics or hospitals in rural and less affluent areas. This thesis concentrates on the aspects of digitisation, compression, and visualisation of medical images.